Depression in dementia - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2001)
BACKGROUND- Dementia and depression are both common disorders of the elderly. it may be difficult to differentiate dementia from depression, and the two conditions commonly coexist. Understanding the relationship between the two disorders is critically important for diagnosis and optimal management of older patients with cognitive impairment and mood changes. REVIEW SUMMARY- Depression may produce cognitive impairment. This cognitive decline, known as the dementia syndrome of depression (DOD), usually is reversed by treatment of the depressive disorder. However, some patients with DOD develop dementia in the following few years. Depression might be a risk factor for Alzheimer disease (AD) or a harbinger of its occurrence. It also may co-occur with AD. Patients with AD and depression differ biologically from those without mood changes. Neuroimaging studies in patients with depression and AD show impaired metabolism in the frontal lobes. Depression exaggerates the functional impairment, decreases quality of life, and increases caregiver distress of patients with AD. In patients presenting with dementia and depression, metabolic imbalances and toxic side effects of drugs should be ruled out. Depression in dementia is treatable with appropriate antidepressant therapy. CONCLUSIONS- Depression and dementia are closely related. Depression can precede, be a risk factor for, or coexist as a part of the clinical presentation of dementia. There are syndrome-specific histopathologic and neurochemical changes in the brains of patients with depression and AD. Depression in dementia is treatable. Treatment of mood changes may help improve functional activity, reduce caregiver distress, and enhance the quality of life of patients.
Keywords: depression; dementia of depression; Alzheimer disease; ALZHEIMERS-DISEASE PATIENTS; MAJOR DEPRESSION; DOUBLE-BLIND; REVERSIBLE DEMENTIA; COGNITIVE DECLINE; RISK FACTOR; SYMPTOMS; PSEUDODEMENTIA; POPULATION; PREVALENCE